Stenocercus bolivarensis Castro & Ayala 1982 (Squamata: Tropiduridae): extensión de su distribución en el departamento de Quindío (Colombia), después de tres décadas de su descubrimiento (2016)
The Bolivar Whorltail Iguana, Stenocercus bolivarensis, is only known in museum collections from six specimens collected in 1982 at its type locality “around Bolivar municipality in the department of Cauca, Colombia”. After three decades of no records in other localities, herein we report a new record of the Bolivar Whorltail Iguana from Quindío department (Armenia municipality), also representing a significant distribution extension of 285 km North from previous records and represents a latitudinal extension of 2.5°. The newly introduced record of S. bolivarensis apparently belongs to an established population. Finally, we discuss the conservation implications of this rediscovery.